First Place Award: Can cefazolin be used in orthopaedic surgery for patients with a self-reported non-IgE mediated penicillin allergy? A prospective case series. Issue 4 (July 2017) - Michaud, Laura; Yen, David
Abstract : Background: Cefazolin is the current recommendation for antibiotic prophylaxis in orthopaedic surgery. However, reported cross-reactivity to first generation cephalosporins in patients with a penicillin allergy ranges from 4% to 18%. In their reports on the rates of cross-reactivity, previous authors have not distinguished IgE from non-IgE reactions. The purpose of this study was to determine the various reactions that are reported as a penicillin allergy and the rate of cefazolin cross-reactivity in patients having only non-IgE reactions to penicillin. Methods: This is a prospective case study of consecutive patients undergoing orthopaedic surgery that had indications for prophylactic antibiotics over a 4-year period. The patients' self-reported specific allergic reactions to penicillin were noted. The reactions were characterized as either IgE or non-IgE mediated. Non-IgE mediated penicillin allergic patients were given cefazolin in the operating room under a controlled setting. Any adverse reaction after the administration of cefazolin was recorded. Results: There were 801 patients. The prevalence of a reported penicillin allergy was 14.1%. Non-IgE mediated reactions accounted for 73.5% of patients reporting a penicillin allergy. Of the 81 non-IgE mediated penicillin allergic patients who received cefazolin, no adverse reactions were reported. Conclusions: It is important to obtain the specific reaction in patients reporting that they are allergic to penicillin to guide the choice of antibiotics. In patients who report a non-IgE reaction to penicillin, it is safe to administer cefazolin.